Investigation for factors affecting the optimum shape of structural components - Kumar, D. Rupesh; Rao, N. V. Ramana (Journal of Structural Engineering, 2025)
This paper deals with the single-objective structural shape optimization of different structural components with prescribed movement directions of shape design variables in different directions. The boundary variation method is used for structural shape optimization of a plate with a circular hole, a plate with a square hole, a connecting rod and a deep beam problem with weight minimization as objective with stress constraints. The results are validated comparing them with the benchmark problems. The effect of - (i) movement directions of shape design variables, (ii) initial shape of opening, (iii) geometric definition and (iv) lower and upper bounds of shape design variables - on (global) optimum shapes are investigated using ANSYS. The discretization errors in the initial as well as optimum shapes are within acceptable limits.